Implementasi Asuhan Keperawatan Komunitas pada Masyarakat Dengan Hipertensi Diabetes Melitus Dan Asam Urat - Safitri, Alfika; Valentine, Geni; Indah, Gia Sastri Permatha; Juliyati, Anisa; Mubarok, Deby; Syahrul Karim, Muhammad; Ashari, Siti Bunga; Febriyanti, Sintia; Aulia, Mustika; Hermawati, Anisa; Shinta (Yayasan Inspirasi El Burhani, 2025)
Introduction: High-risk groups that aim to improve health through promotive and preventive efforts without neglecting curative and rehabilitative by involving the community as a partner in solving health problems that occur in the community. Objective: Implement the results of the formulation of community nursing action plans to the communityMethod: The assessment that has been carried out on Tuesday, June 3, 2025 has collected data in RW 10 Gebang Raya. Data collection of RW 10 with a total population of 306 households with samples using the slovin formula was obtained with the results of 75 households.Result: This community nursing activity was carried out in RW 10 Gebang Raya Village, Periuk District, Tangerang City, from June 2 to July 4, 2025 with a participatory approach. Based on the study data, it was found that the main health problems were hypertension (33.33%), diabetes mellitus (22.67%), gout (16%), cholesterol (8%), stroke (5.33%), ulcers (2.67%), and others (12%). The activities are focused on hypertension education, demonstration and administration of tomato juice as complementary therapy, diabetes mellitus (DM) education and exercises, as well as education about gout. Conclusion: The community is able to implement the directions given by students well. The implementation of nursing carried out on the elderly includes: Reduce high blood pressure, lower uric acid levels and reduce blood sugar levels From this activity, there have been significant changes in public health conditions, especially in the elderly.